Rancang Bangun Simulasi Parkir Mobil Berbasis Mikrokontroler ESP 8266 dan Monitoring Menggunakan Blynk - Agung Supriyadi; Lukman Aditya; Ujang Wiharja (Teknik Elektro Universtias Krisnadwipayana, 2025)
The aim of this research is to design and simulate an automatic car parking system based on the ESP 8266 microcontroller in order to improve the efficiency of parking slot monitoring. Conventional parking systems are generally operated manually, which often results in time inefficiency and difficulty in determining available capacities. The proposed design applies an Internet of Things (IoT) approach by integrating several components into a prototype simulation. The ESP 8266 microcontroller serves as the main controller, connected to infrared sensors that detect vehicle presence. A servo motor operates as the parking barrier, while an ESP 32-CAM module enables visual monitoring of the parking area. In addition, a 20x4 LCD displays the number of available slots, vehicle entry and exit status, and real-time date and time. Sensor data are also transmitted to the Blynk application for real-time monitoring and control via smartphones. Simulation testing was conducted to evaluate system functionality. The infrared sensors, with a 10 cm detection range, achieved an average response time of 1.24 seconds for barrier operation. The servo motor successfully opened at a 90-degree angle with 2 watts of power consumption and a movement speed of 1.02 seconds. The LCD displayed accurate slot availability and real-time updates, while the Blynk application provided reliable monitoring and system indicators. The ESP 32-CAM ensured continuous visual observation of the parking area, and a buzzer alarm was triggered when vehicles attempted to enter during full-capacity conditions. In conclusion, the design and simulation of the system demonstrate its potential to enhance parking management by reducing manual supervision, enabling real-time monitoring, and increasing convenience for both drivers and parking operators.